EXPERIENCE OF LONG TERM EEG AND ECG MONITORING IN THE DIAGNOSTIC OF PAROXYSMAL EVENTS EPILEPTIC AND NON EPILEPTICS SEIZURES - V. V. Gnezditskiy; V. A. Karlov; O. S. Korepina; A. A. Skomarohov (Эпилепсия и пароксизмальные состояния, 2016)
Abstract: ambulatory or Holter EEG (AMEEG) are the prolonged record EEG and number of polygraphist indices under the natural conditions of the behavior of man during the active, wakefulness and the sleep. Its role in the clinical practice is thus far insufficiently studied. Purpose of the work to generalize the experience of the application of long-term monitoring EEG in the neurologic practice and to show his possibility and limitations. In the work shown its value for the clinical practice on the basis of the generalization of the experience of conducting AMEEG in the Research Center of neurology. We generalized the experience of the examiner of 354 patients with the aid of AMEEG with a duration of inspection of from 3 to 24 h. Of 354 patients in 231 was conducted ambulatory monitoring, in 58 – ward monitoring EEG, in 65 reanimation monitoring EEG and polygraphist indices in resuscitation or ward of intensive care. The inspection of patients was carried out with the aid of the compact EEG- recording “Ensefalan-EEGR-19/26” of Medicom-MTD firm (Taganrog). It is shown in the concrete examples, that the ambulatory monitoring EEG considerably enlarges the possibilities of inspection EEG and poligraphic indices and it makes it possible to obtain new information about the state of the brain. In diagnostics of epilepsy, with differential diagnostics of the epileptic and non epileptic forms of paroxysm, and prolonged monitoring makes it possible to improve diagnostics. Under resuscitation conditions the monitoring EEG makes it possible to more fully reveal changes in patients, who be in a reactive (critical) state; during the ward monitoring of – to answer the number of the questions, connected with the differential-diagnostic tasks, which appear in the neurologic practice. With the aid of AMEEG it is sufficiently easy to carry out polisomnografic research, without resorting to the bulky systems (they are not necessary special ward, the expensive equipment).